INTEGRATION OF ESP32-CAM WITH ANDROID AND IOT BASED ENGLISH-INDONESIAN TRANSLATION APPLICATION USING OCR TECHNOLOGY - Nurhaliza, Siti; Putri, Kirana Alyssa; Iqlimah Attyyatullatifah; I’zaaz Akhdan Muhadzdzab; Atiqah Meutia Hilda (Jurnal Teknik Informatika (Jutif), 2024)
Language is a constant element in global human interaction, particularly English. This research presents the design and development of an innovative Android and IoT-based translation application, which facilitates seamless English-Indonesian translation. By utilizing Optical Character Recognition (OCR) technology for text input, the app is enhanced by the integration of ESP32-CAM, a versatile microcontroller with a camera module. This unique combination promises accurate and efficient translation, bridging language barriers while exploring the potential of the Internet of Things (IoT) in linguistic applications. This research reveals the intricate process of creating this translator tool, using the Dart programming language and Flutter framework in Android app development, with the support of Visual Studio Code as the software development environment, as well as the Arduino IDE for the ESP32-CAM microcontroller. It shows how OCR technology and ESP32-CAM significantly enhance the translation experience in an increasingly connected world.